The challenges and prospects of using altmetrics to measure research outputs - Abiodun, Akinwande Kazeem
Altmetrics is a new metric system that focuses on tracking online public engagements with any research output. The system is a new research metric and evaluation system that help researcher to identify and understand the amount of public engagement with their research outputs and get feedback on their research. The system provides accelerated feedback to researchers on the performance of their research and scholarly outputs shortly after the publication of such research outputs. This is done through the system's data sources like Twitter, Facebook, Blog platforms, News platforms, Mendeley, CiteULike, Reddit, Web of Science, Scopus, and other social, academic, and research related platforms which the system track. This research investigated the challenges and prospects of using altmetrics to measure research outputs, views of researchers about altmetrics, and the ability of the system to evaluate research outputs. The survey research design was adopted for this research with qualitative method of data collection using the semi-structured self-developed interview questions as the research instrument. The surveyed respondents were 7 professors in the fields of sciences and social sciences, and are expert researchers with minimum of 15 years of academic and research experiences. The results revealed that although, altmetrics is a novel metric system for research and scholarly outputs evaluation. Nonetheless, it is a welcome innovation that should be considered to track and evaluate the performance and amount of public engagement with research outputs based on its various prospects. Further findings of the research also revealed that although, little seems to be known about the metric system among researchers in the studied institution for this research, however, the prospective adoption and use of the system by researchers and scholars comes with the benefit of early information about the performance and impact of their research outputs. Also, increased citation, increased visibility, ease of awareness about research outputs and comprehensives of the system's data sources are some of the additional prospects of altmetrics as revealed by the findings of this research. Meanwhile, some of the challenges that were identified as parts of the limitations of the system were lack of awareness about the system, word limit and related technical specifications on social media (Twitter and others), gaming, artificial download, sponsored like and share, robot tweeting and retweeting, IP routing and others. Hence, the research concluded and recommended that the system's administrators should continuously strive to improve the system, especially the system's social media data sources from time to time by ensuring quality control and adequate check and balances on the social media data sources and other related data sources of the system. More importantly, the system's management should embark on active awareness and campaign drive to acquaint members of the public, especially the academicians, researchers, and scholars about the system and the related benefits that are attached to its adoption and use for tracking and evaluating the performance and impacts of their research outputs.